Diverse roles of EV-RNA in cancer progression. (October 2021) - Cocks, Alexander; Martinez-Rodriguez, Verena; Del Vecchio, Filippo; Schukking, Monique; Broseghini, Elisabetta; Giannakopoulos, Stefanos; Fabbri, Muller
Abstract: Extracellular vesicles (EVs) have emerged as important players in all aspects of cancer biology. Their function is mediated by their cargo and surface molecules including proteins, lipids, sugars and nucleic acids. RNA in particular is a key mediator of EV function both in normal and cancer cells. This statement is supported by several lines of evidence. First, cells do not always randomly load RNA in EVs, there seems to be a specific manner in which cells populate their EVs with certain RNA molecules. Moreover, cellular uptake of EV-RNA and the secondary compartmentalization of EV-RNA in recipient cells is widely reported, and these RNAs have an impact on all aspects of cancer growth and the anti-tumoral immune response. Additionally, EV-RNA seems to work through various mechanisms of action, highlighting the intricacies of EVs and their RNA cargo as prominent means of inter-cellular communication.